Seed system security assessment: Southern Sudan - International Center for Tropical Agriculture; Food and Agriculture Organization of the United Nations; Ministry of Agriculture and Forestry, South Sudan; Africa Action Help International; Agency for Technical Cooperation and Development; Adventist Development and Relief Agency; Amanda Magra Universal Relief Team; Danish Refugee Council; Norwegian People's Aid; Catholic Relief Services (FAO and CIAT, 2011)
A Seed System Security Assessment (SSSA) was carried out across Southern Sudan in November–December 2010. It reviewed the functioning of the seed systems farmers use, both formal and informal, and assessed whether farmers could access seed of adequate quantity and quality in the short and medium term. The work covered 8 states and 16 counties, chosen to anticipate the range of possible seed security constraints. Field research encompassed 885 farmer interviews, seed/grain market analysis, interviews with 70 traders, over 25 focus group discussions (including discussions with women’s groups), and key-informant sessions. Background papers were also commissioned on: a) the formal breeding sector’s structures and processes; b) the formal seed sector’s structures and processes; and c) current decentralized seed multiplication and distribution initiatives. This is among the more comprehensive agricultural and seed security assessments carried out nationwide, across Southern Sudan, in many decades.